Rare Earth Element Content in Fructus Sophorae from Different Areas - Wang, Xiaojing; Li, Yumei (Asian Journal of Chemistry, 2012)
Fructus sophorae is traditional Chinese medicinal herb. Fructus sophorae samples were collected from eleven areas of Dezhou and digested with various acids followed by ICP-MS analysis for 14 kinds of rare earth elements. The contents of total rare earth elements in Fructus sophorae samples from different areas ranged from 0.6826 μg/g to 1.0527 μg/g and the determined content of rare earth elements in Fructus sophorae varied from one area to another. The distribution tendency of rare earth elements was identical with Odd Harkin's rule. The plots of normalized element concentration versus atomic number showed some characteristic distribution tendencies. The geology condition and natural environment should be responsible for the difference, but the allocation mechanism of rare earth elements in Fructus sophorae should be further studied. Content and distribution of rare earth elements in Fructus sophorae were compared with that in Flos sophorae.